Disseminated histoplasmosis complicated by concurrent opportunistic infections in a person living with HIV (PLHIV) — The need for infectious disease high dependency units in the United Kingdom. (January 2020) - Farooq, Hamzah Z.; Arfeen, Faraz; Davies, Craig; Ahmad, Shazaad; Ajdukiewicz, Katherine M.B.
Abstract: We describe an immunocompromised HIV patient with disseminated histoplasmosis, cerebral toxoplasmosis, Pneumocystis jirovecii pneumonia (PJP) with cytomegalovirus (CMV) and Human Herpes virus 8 (HHV8) viraemia complicated by severe thrombocytopenia and hypocalcaemia. During a prolonged inpatient admission at our infectious disease (ID) high care unit (HCU), he represented a diagnostic challenge and management dilemma involving a variety of medical specialties. We aim to explore the difficulties surrounding the diagnosis and management of disseminated histoplasmosis especially in view of other concurrent opportunistic infections (OIs). We aim to elaborate on how this rare case provided new insight into the management of multiple OIs in a severely immunocompromised HIV individual and why we need specialist ID high dependency units. Highlights: A HIV positive African gentleman with a history of tuberculosis was admitted to a regional infectious disease (ID) unit following a cardiac arrest. His inpatient stay was complicated by severe thrombocytopenia and hypocalcaemia requiring multiple transfusions. His end-diagnoses are disseminated histoplasmosis, cerebral toxoplasmosis, Pneumocystis jirovecii pneumonia (PJP), CMV and HHV-8 viraemia. This case represents the need for specialist ID units to ensure the best quality of care for ID patients in the United Kingdom.